Mahlers Mater Dolorosa - Amerongen, Martin van 1941-2002 (Amsterdam De Arbeiderspers, 1992)
Gustav Mahler confronts his wife Alma about her extramarital affair with architekt Walter Gropius. Alma reacts furiously, accusing him of pouring his soul into his symphonies while she has nothing else. When Mahler finds her diary, he reads in it how torn and desperate she has felt. With this background, Mahler boards the train to Leiden to consult Sigmund Freud. During their walk, Freud soon notices how much Mahler must have felt connected to his mother in a very specific way as a child.
Reconstruction of the meeting between Sigmund Freud and Gustav Mahler in Leiden in 1910.
Keywords: Mahler, Gustav -- 1860-1911; Mahler, Alma -- 1879-1964; Freud, Sigmund -- 1856-1939; Music history; Novel